(untitled) (Gestão & Regionalidade, 2016)
This paper aims to analyze the international academic literature on the collaborative management in supply chain in articles published in international journals indexed in ISI Web of Knowledge. The survey covered a period of ten years (2005-2014), with 63 articles analyzed, using bibliometric techniques to analyze: year of publication, journals where these articles were published, authors with more publications, more accessible articles, and the identification of the major works in collaborative management in supply chains. The survey results indicate that there is a predominance of publications in few journals, and that there are many authors with only one published article on the subject.